Sifat Fisik dan Aktivitas Antioksidan Dendeng Daging Sapi dengan Penambahan Stroberi (Fragaria ananassa) sebagai Bahan Curing (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Nitrate or nitrite that used on dendeng making as antioxidant agent and color stabilizer could forming toxic compound (nitrosamine). The Formation of nitrosamine could be inhibited by addition of natural antioxidant that contained in the fruits such as strawberry (Fragaria ananassa). The aim of this study was to evaluate the influence of stawberry as curing ingredient on physical properties and antioxidant activity of dendeng. Dendeng was made by addition of spices and combination of nitrite (0 ppm and 125 ppm) and strawberry (0%, 10%, 20%, 30%) addition. Sample for analysis used fried dendeng. The result showed that pH value  were  affected  by  additon  of  nitrite  and  strawberry    (P